Cooperation between India and Central Asia and its importance for the region - Movkebayeva, G.A.; Sadvakassova, A.M. (KU Publ., 2021)
The article examines the main aspects of cooperation between India and Central Asian states, their strategic foundations, the main sectoral areas of relations with the region, the dynamics of the development of bilateral and regional relations. Modern relations between countries such as India and the Central Asian region are characterized by dynamic global processes that significantly affect the world order. India has shown an interest in strengthening its diverse relations with the Central Asian region. In this context the authors examined the foreign policy of India on official statements, speeches, comments and joint statements, as well as programs such as “Look East”, “Gujral Doctrine”, “Extended Neighborhood” and “Connect Central Asia” strategies that prove India's growing interest in the region. An analysis was also made of the agreements signed during official high-level visits to the republics of Central Asia and India. Statistical work was carried out on the trade turnover of India with the countries of Central Asia, and their indicators were compared in the form of a table. The article discusses cooperation that covers various areas, such as security, energy, technology, education, transport, and others. Nowadays, relations are developing both on a bilateral basis and within the framework of various organizations in the field of economy and security. An analysis of India's policy in the Central Asian region is made, and the existing risks and benefits of this cooperation are listed.
Үндістан мен Орталық Азия арасындағы ынтымақтастық жəне оның аймақ үшін маңызы
Сотрудничество между Индией и Центральной Азией и его значение для региона
Keywords: Central Asia; India; geopolitics; security; economic cooperation; One Belt—One Road; threats; Extended neighborhood; “Connect Central Asia”; strategic interests; soft power